Synthesis and improved electrochemical properties of Li2MnSiO4 cathodes - Aravindan, Vanchiappan (2011)
Superior performance Li2MnSiO4 cathodes with flower-like morphology are prepared by hydrothermal route for the first time. An x-ray diffraction pattern confirms the formation of the orthorhombic structure with Pmn21 space group. The prepared Li2MnSiO4 materials are subjected to heat treatment at 700 °C to achieve complete crystallization in the presence of adipic acid. The Li/Li2MnSiO4 cells delivered an initial discharge capacity 73 and 100 mAh g−1 for as-synthesized and heat-treated Li2MnSiO4, respectively. It is surprising to note that heat-treated Li2MnSiO4 exhibits more stable and superior cycling performance than reported values elsewhere, which is due to the unique morphology as well as carbon coating derived from the carbonization of adipic acid.